Do youth mentoring programs change the perspectives and improve the life opportunities of at-risk youth? - Núria Rodríguez-Planas (IZA World of Labor, 2014)
Mentoring programs such as Big Brothers Big Sisters of America have been providing positive role models and building social skills for more than a century. However, most formal mentoring programs are relatively novel and researchers have only recently begun to rigorously evaluate their impact on changing at-risk youth's perspectives and providing opportunities for them to achieve better life outcomes. While a variety of mentoring and counseling programs have emerged around the world in recent years, knowledge of their effectiveness remains incomplete.
Keywords: C93; I21; I22; I28; J24; 330; at-risk youth; noncognitive skills; social barriers; resilience